Targeted drug distribution in tumor extracellular fluid of GD2-expressing neuroblastoma patient-derived xenografts using SN-38-loaded nanoparticles conjugated to the monoclonal antibody 3F8 - Monterrubio, Carles (2017)
Neuroblastoma is a pediatric solid tumor with high expression of the tumor associated antigen disialoganglioside GD2. Despite initial response to induction therapy, nearly 50% of high-risk neuroblastomas recur because of chemoresistance. Here we encapsulated the topoisomerase-I inhibitor SN-38 in polymeric nanoparticles (NPs) surface-decorated with the anti-GD2 mouse mAb 3F8 at a mean density of seven antibody molecules per NP. The accumulation of drug-loaded NPs targeted with 3F8 versus with control antibody was monitored by microdialysis in patient-derived GD2-expressing neuroblastoma xenografts. We showed that the extent of tumor penetration by SN-38 was significantly higher in mice receiving the targeted nano-drug delivery system when compared to non-targeted system or free drug. This selective penetration of the tumor extracellular fluid translated into a strong anti-tumor effect prolonging survival of mice bearing GD2-high neuroblastomas in vivo.